2008
DOI: 10.1093/ndt/gfm591
|View full text |Cite
|
Sign up to set email alerts
|

The impact of acute kidney injury on short-term survival in an Eastern European population with stroke

Abstract: The mean age of this population was 66.1 +/- 11.5 years, 49.3% were males, mean glomerular filtration rate (GFR) 68.9 +/- 22.6 ml/min/1.73 m(2). The 30-day mortality rate was 17.2%. One hundred and fifty-eight patients presented with haemorrhagic stroke and 932 patients had ischaemic stroke. Stroke mortality was-14% for ischaemic stroke and almost twice as high for haemorrhagic stroke-36.3%. One hundred fifty-eight (14.5%) patients were classified as developing AKI. The AKI patients were older, had a higher ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 24 publications
9
77
2
3
Order By: Relevance
“…Majority of the study subjects, (128, 53.33%) and majority of the AKI patients (20, 54.05%) belonged to > 60 years age group. ese ndings were comparable to the study of Covic et al, 2008. ey have showed in their study that the mean age of the study subjects was 66.1±11.5 years.…”
Section: Discussionsupporting
confidence: 85%
“…Majority of the study subjects, (128, 53.33%) and majority of the AKI patients (20, 54.05%) belonged to > 60 years age group. ese ndings were comparable to the study of Covic et al, 2008. ey have showed in their study that the mean age of the study subjects was 66.1±11.5 years.…”
Section: Discussionsupporting
confidence: 85%
“…It must be emphasized that there are several causes of decreased eGFR; it could represent acute dehydration on admission, a concurrent infection, or renal artery stenosis as well as small vessel renovascular disease. Because acute renal failure itself is an independent prognostic factor for mortality after stroke, 40 our results may underestimate the prognostic value of chronically lowered eGFR. To avoid bias from low eGFR (Ͻ30 mL/min/1.73 m 2 ), 5 patients were excluded from the analysis.…”
Section: Oksala Et Almentioning
confidence: 71%
“…Only a recent retrospective study investigated the incidence and characteristics of AKI in patients with stroke in an Eastern European population and its role on short-term mortality (20). The authors reported a 14.5% incidence of AKI that was associated with an increased 30-d mortality (43.1 versus 12.8% in patients without AKI).…”
Section: Discussionmentioning
confidence: 99%